2017
DOI: 10.1002/jcc.24728
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of consensus binding mode geometries for related chemical series of positive allosteric modulators of adenosine and muscarinic acetylcholine receptors

Abstract: Following insights from recent crystal structures of the muscarinic acetylcholine receptor, binding modes of Positive Allosteric Modulators (PAMs) were predicted under the assumption that PAMs should bind to the extracellular surface of the active state. A series of well-characterized PAMs for adenosine (A1R, A2AR, A3R) and muscarinic acetylcholine (M1R, M5R) receptors were modeled using both rigid and flexible receptor CHARMM-based molecular docking. Studies of adenosine receptors investigated the molecular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…In a previously published assessment of docking accuracy, these CHARMM-based docking methods were shown to have the highest “discriminative power”to correctly predict binding geometries over diverse classes of protein-ligand interactions compared to other common scoring functions [ 83 , 84 ]. Molecular docking utilized the LPDB CHARMm force field [ 85 , 86 ], the Linear Interaction Energy (LIE) scoring approach to approximate the free energy of binding (ΔG bind ) has been previously described [ 84 , 87 ] and have also been specifically assessed for their use in calculating ligand efficiencies in computational medicinal chemistry applications [ 84 ]. For aromatic pharmacophore sites selected for being sufficiently favorable, computational fragment screening was performed using identified benzene coordinates as X,Y,Z center of mass reference positions.…”
Section: Methodsmentioning
confidence: 99%
“…In a previously published assessment of docking accuracy, these CHARMM-based docking methods were shown to have the highest “discriminative power”to correctly predict binding geometries over diverse classes of protein-ligand interactions compared to other common scoring functions [ 83 , 84 ]. Molecular docking utilized the LPDB CHARMm force field [ 85 , 86 ], the Linear Interaction Energy (LIE) scoring approach to approximate the free energy of binding (ΔG bind ) has been previously described [ 84 , 87 ] and have also been specifically assessed for their use in calculating ligand efficiencies in computational medicinal chemistry applications [ 84 ]. For aromatic pharmacophore sites selected for being sufficiently favorable, computational fragment screening was performed using identified benzene coordinates as X,Y,Z center of mass reference positions.…”
Section: Methodsmentioning
confidence: 99%
“…Structural modeling was performed with our established methods (48). Figures were prepared based on structures of myristoylated PKAc (PDB code 4DFX) (14).…”
Section: Modeling Structurementioning
confidence: 99%
“…With the allosteric modulation of M 5 garnering interest, the Armen group conducted computational investigations into modes of binding for M 5 PAMs and NAMs ( 10 and 15 , respectively) . Homology models of human M 5 and human M 1 were constructed in a similar fashion to that utilized by Zheng et al Using the reported crystal structure of hM 2 simultaneously bound to the agonist iperoxo and the nonselective PAM LY2119620, it was shown that 10 occupies a binding site analogous to PAMs at human M 1 .…”
Section: Selective Modulation Of M5mentioning
confidence: 99%